Lower utilization of home blood pressure monitoring in younger, poorly educated hypertensive males – real-life data - Anna Chudek; Aleksander Jerzy Owczarek; Joanna Ficek; Agnieszka Almgren-Rachtan; Jerzy Chudek (Blood Pressure, 2020)
Background: Home blood pressure monitoring (HBPM) became a standard in the management of hypertension. However, there are few data concerning the utilisation of blood pressure (BP) monitors in daily clinical practice. Aim: The aim of this analysis was to show: (1) how frequently hypertensive patients are equipped with BP monitors, (2) how often they perform regular HBPM and running BP diaries, (3) what are the correlates of utilisation of BP monitors, in a large real-life cohort of hypertensives examined for the efficacy of antihypertensive therapy. Patients and methods: The survey was conducted by 570 physicians among 14,200 hypertensive patients, of whom 12,289 (6163 women; mean age 63 ± 12 years) declared use of antihypertensive medicines. Each patient was asked whether at home is having and using regularly or occasionally BP monitor and running BP diary. BP control was assessed based on the mean of two attended office BP measurements. Results: Among patient equipped with BP monitors (87.2%), 73.4% were conducting HBPM regularly, while 26.6% occasionally, and 66.9% were running BP diaries. Controlled BP was achieved by 34.5% (32.9% men and 36.1% women; p < .001), more frequently by equipped with BP monitors (34.9 vs 31.7%, p < .001). Female sex, education, professional activity, active lifestyle, older age, hypertensive polytherapy, longer than 5-year therapy for hypertension, and coexistence of diabetes were factors increasing, while alcohol consumption, visceral obesity and heart failure decreasing the probability of being equipped with BP monitor and running BP diary. Regular HBPM were more frequently among women, physically active, older, diabetics, viscerally obese and patients with coronary artery disease. Conclusions: (1) The majority of hypertensive Poles are already equipped with BP monitors, (2) three-fourth patients perform regular HBPM and two-third run BP diaries, (3) there is still a need to promote utilisation of BP monitors among younger, poorly educated hypertensive males.